2010
DOI: 10.1007/s10238-010-0094-5
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic profiling of renal allograft rejection in serum using magnetic bead–based sample fractionation and MALDI-TOF MS

Abstract: Proteomics is one of the emerging techniques for biomarker discovery. Biomarkers can be used for early noninvasive diagnosis and prognosis of diseases and treatment efficacy evaluation. In the present study, the well-established research systems of ClinProt Micro solution incorporated unique magnetic bead sample preparation technology, which, based on matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF MS), have become very successful in bioinformatics due to its outstanding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…Conversely, tax cuts, which reduced the price of alcohol in Finland, were associated with increased alcohol-related mortality [11]. However, despite this, the price of alcohol continues to decline in real terms in many European countries [12,13]. …”
Section: Introductionmentioning
confidence: 99%
“…Conversely, tax cuts, which reduced the price of alcohol in Finland, were associated with increased alcohol-related mortality [11]. However, despite this, the price of alcohol continues to decline in real terms in many European countries [12,13]. …”
Section: Introductionmentioning
confidence: 99%
“…Subsequent construction of transcription regulation networks identified NF-κB, STAT1, and STAT3 as key transcription regulators in acute rejection [36]. Further small-scaled clinical proteomic studies detected serum peptide fingerprints that distinguish acute and chronic rejection [37] and acute rejection from acute tubular necrosis [38]. Just recently, Cibrik et al identified a plasma protein signature of 17 protein biomarkers for patients with acute renal allograft rejection.…”
Section: Acute Renal Allograft Rejectionmentioning
confidence: 95%
“…Since biomolecular profiling will reflect changes in developmental, physiological, and pathological processes [178][179][180][181][182][183][184][185], several approaches have used bimolecular profiling for valid clinical diagnoses. Multivariate analysis such as principal component analysis (PCA) is often involved in these approaches to efficiently identify differences in biomolecular patterns between samples [186,187].…”
Section: Detecting Disease Biomarkers In Biological Fluidsmentioning
confidence: 99%